1974
DOI: 10.1136/bmj.4.5947.733
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Distribution of Digoxin in Human Heart

Abstract: SummaryUsing the recipient's human heart removed at cardiac transplantation, the distribution of digoxin at both the cellular and subcellular level has been studied. In the presence of diffuse histological myocardial abnormalities tissue digoxin is decreased, but the subcellular distribution, presumably reflecting binding to a possible receptor site, is uniform. When the histological abnormality is focal then digoxin distribution is uniform.These results suggest that in the presence of myocardial ischaemia pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…The predominant role in taking up digoxin molecules is said to be played by myocardial cells rather than by connective tissue and fat [106]. A direct relationship between digoxin concentration in plasma and concentration in the heart cell microsomal fraction was found [107], since the latter may be related to the inotropic effect [108]. However, the total levels in the myocardium were also widely investigated.…”
Section: Cardiac Pharmaceutical Agentsmentioning
confidence: 99%
“…The predominant role in taking up digoxin molecules is said to be played by myocardial cells rather than by connective tissue and fat [106]. A direct relationship between digoxin concentration in plasma and concentration in the heart cell microsomal fraction was found [107], since the latter may be related to the inotropic effect [108]. However, the total levels in the myocardium were also widely investigated.…”
Section: Cardiac Pharmaceutical Agentsmentioning
confidence: 99%
“…Cardiac transplantation has afforded a very special opportunity to study the distribution of digoxin in the human heart because samples from the recipient's organ can be analysed with both the timing of the last digoxin dose known and a plasma sample taken after induction of anaesthesia, and before cardiopulmonary bypass. In such a study of 7 transplant recipients' hearts, Coltart et al (1974) found no consistent relation between plasma concentrations and tissue concentrations of digoxin in samples from each of the cardiac chambers. Moreover, in the presence of diffuse histological abnormalities of the myocardium, tissue digoxin was decreased and such structural inhomogeneity seemed at least partly to account for disparities in tissue concentrations within individual hearts.…”
mentioning
confidence: 92%
“…In recipients' hearts removed at cardiac transplantation, Coltart et al (1974) found that in the presence of diffuse histological abnormalities of the myocardium, tissue digoxin concentrations were decreased, but in 3 hearts microsomal fraction digoxin concentrations in samples from various parts of the heart were uniform. Thus, the inhomogeneity of tissue digoxin concentrations in these diseased and malfunctioning hearts is not paralleled by site-to-site disparities of microsomally bound digoxin and this presumably reflects uniformity of binding to the possible receptor site.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Relationships between drug response and digoxin concentrations in blood, myocardium and receptor site are becoming more clearly defined [17,42,51,52] and there is a consensus of opinion that the serum digoxin concentra tion provides an useful aid in achieving therapeutic doses. Although appre ciable overlap between toxic and nontoxic levels has been the usual experience, mean serum concentrations in a number of series are about twofold higher in patients with cardiac disease who had evidence of toxicity than in those without such evidence [17] (fig.…”
Section: Therapeutic Range O F Sdcmentioning
confidence: 99%